2015
DOI: 10.1038/onc.2015.374
|View full text |Cite
|
Sign up to set email alerts
|

TAMing resistance to multi-targeted kinase inhibitors through Axl and Met inhibition

Abstract: TAM (Tyro3-Axl-Mer) receptor tyrosine kinases and Met are implicated in several hallmarks of cancer progression including sustained angiogenesis, enhanced motility, tissue invasion and acquisition of metastatic potential through the upregulation of epithelial-to-mesenchymal transition. Increasing evidence has confirmed Axl and Met as emerging central drivers of adaptive resistance to targeted therapies across a wide variety of cancers. In this issue of Oncogene, Zhou et al. describe the mechanisms linking Axl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…These data were consistent with findings that AXL is a critical player in the metastatic potential and overall prognosis of numerous other solid cancers [7-11]. Binding of AXL to its only ligand, growth arrest specific gene-6 (GAS6), induces proliferation, survival, invasion, metastasis, avoidance of apoptosis, and angiogenesis in other tumor types [12, 13], though no activating mutation has been identified in AXL [14]. AXL acts through a number of downstream pathways, including the PI3K/AKT and Ras/ERK pathways [15].…”
Section: Introductionsupporting
confidence: 89%
“…These data were consistent with findings that AXL is a critical player in the metastatic potential and overall prognosis of numerous other solid cancers [7-11]. Binding of AXL to its only ligand, growth arrest specific gene-6 (GAS6), induces proliferation, survival, invasion, metastasis, avoidance of apoptosis, and angiogenesis in other tumor types [12, 13], though no activating mutation has been identified in AXL [14]. AXL acts through a number of downstream pathways, including the PI3K/AKT and Ras/ERK pathways [15].…”
Section: Introductionsupporting
confidence: 89%
“…In most of these cases, aberrant overexpression of TAM receptors is observed; mutations in TAM receptors are an exception [19]. Mechanistically, TAM receptor signaling supports several key cellular events in the tumor, from cell growth and survival, to metastasis, epithelial-mesenchymal transition (EMT), and resistance to chemotherapy [20,22,23,24,122,123,124,125]. Importantly, experimental evidence demonstrates that TAM antagonism can efficiently revert these processes [22,126,127,128,129,130], underscoring the potential benefits of TAM inhibition for cancer therapy (Figure 3).…”
Section: Taming Anti-tumor Immunitymentioning
confidence: 99%
“…Notably, targeted inhibition of TAM signaling has proven to have robust anti-tumor efficacy in diverse experimental cancer settings. These results have encouraged a heated race in the development of novel and specific ways of inhibiting TAM signaling for use in cancer patients [24]. In fact, small-molecule kinase inhibitors, monoclonal antibodies, and soluble decoy TAM receptors are currently under development [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Axl is known to be indirectly under transcriptional control of VHL through hypoxia-inducible factors 27. Recent work has implicated Axl in the acquisition of resistance to antiangiogenic therapy, and revealed its contribution in driving metastatic spread and poorer survival 3 72. Recent large-scale phase III trials of TKI endowed with Axl inhibitory properties have confirmed Axl as a therapeutic target in RCC 73…”
Section: The Role Of Axl In Cancer Progressionmentioning
confidence: 99%
“…Evidence suggesting the oncogenic potential of Axl has been ever-present from the point of its initial isolation from chronic myelogenous leukaemia (CML) 1. Further work into the functionality of this gene has shown its mechanistic involvement in determining a wide variety of cancerous hallmarks including: proliferation, survival, evasion from apoptosis, enhanced angiogenesis, invasiveness and, more recently, resistance to targeted anticancer therapies 2 3. Furthermore, Axl has been shown to influence the clinical behaviour of a number of cancer histotypes, holding prognostic significance in breast, lung, ovarian, renal, gastrointestinal cancers as well as many other solid and haematopoietic malignancies.…”
Section: Introductionmentioning
confidence: 99%